MODAL SOSIAL PADA KELOMPOK TANI PADI SAWAH DI DESA KASUMEIA KECAMATAN ONEMBUTE KABUPATEN KONAWE - Rahman, Ihzam Nur; Taufik, Yani; Hamzah, Awaluddin (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
Strong social capital is key to increasing the empowerment of farmers and the effectiveness of farmer groups in facing various structural challenges in the agricultural sector, including weak institutional capacity, land fragmentation, and low levels of trust at the rural level. This study aims to determine the level of farmers' social capital, the role of farmer groups, and the relationship between social capital and the role of farmer groups in the development of rice farmers in Kasumeia Village, Konawe Regency. The population size of each farmer group varied, so the sample size was determined using purposive sampling. Three farmers were selected as samples from each farmer group, consisting of the farmer group leader, an active farmer, and a passive farmer. A total of nine farmers were selected as respondents for the study, three farmers from each farmer group. Data collection for the research was carried out using several methods, namely a survey method using questionnaires, interviews, and documentation. The variables in this study included social capital and the role of farmer groups. The data were analyzed using descriptive analysis methods. The results showed that the social capital of farmers in Kasumeia Village was relatively high, particularly in terms of trust, social networks, and social norms or values. Farmer groups in Kasumeia Village have played a significant role as learning classes and vehicles for cooperation. However, the role of groups as production units still faces challenges in terms of resource management efficiency, market access, and information distribution. There is a significant (0.005) and strong (0.681) relationship between farmers' social capital and the role of farmer groups. Social capital such as trust, norms, and networks has proven to be a determining factor that strengthens cooperation and the effectiveness of farmer group functions. However, despite this strong relationship, the implementation of farmer group functions has not been fully maximized because there are still members who participate only to a limited extent.